Kajian Teo-Filosofis pada Upacara Masegeh dengan Sarana Sapi Jantan di Desa Tambakan Kabupaten Buleleng - I Ketut Wardana Yasa; I Nengah Alit Nuriawan (Jayapangus Press, 2022)
The use of cows at the masegeh ceremony is a religious system in which it cannot be separated from the discussion of aspects of divinity or theology, philosophy, scriptures, ceremonial processes, ceremonial facilities, prayers or mantras, people, ceremonial places and so on as well as the adherents' community, as well as their implications for life. The purpose of this study is to describe that the masegeh ceremony using bulls in Tambakan Village, Buleleng Regency has profound theo-philosophical implications or meanings for people's lives in Tambakan Village, Buleleng Regency, Bali. This research uses research methods, such as observation, interviews with religious and community leaders involved in the masegeh ceremony, literature study, and documentation study. The presentation of the data is carried out in a descriptive analysis because the data that has been collected will then be described thoroughly from its various parts and examine the parts themselves and the relationship between the parts to obtain the right understanding and understanding of the overall meaning in accordance with the problems solved in order. The results of the study will describe 3 main things, namely the first the origin of the masegeh ceremony, then the second discussion regarding the local belief that the use of cows in the masegeh ceremony is able to eliminate the epidemic and the third discussion regarding the terminology of theo-philosophical studies in the masegeh ceremony. So from the results of this study it can be concluded that the causes of the use of cows at the mesegeh ceremony at Prajapati Temple include several things, namely (1) the existence of the Masesangi tradition of giving bulls at Dalem Temple, Pakraman Tambakan Village; (2) There is a local belief that the use of cows in the masegeh Ceremony is able to eliminate the epidemic; (3) The implications of the use of cows in the mesegeh ceremony in Pakraman Tambakan Village have two significant impacts, namely the Theo-philosophical Implications as the realization of the divine concept of Shiva Siddhanta by worshiping Shiva as Yamarudra, and the liberation that cow sacrifice is actually a sacrifice of the animal nature in oneself.